Experiment analysis of non-uniformity measurement by array detector scanning system - Napat Watjanatepin; Patcharanan Sritanauthaikorn; Chaiyant Boonmee; Paiboon Kiatsookkanatorn; Sarayoot Thongkullaphat; Suvinai Sodajaroen (Institute of Advanced Engineering and Science, 2022)
Solar simulator is used to analysis characteristic of the solar cells. The non-uniformity is its major performance. The traditional non-uniformity measurement calls single detector method. The paper’s objective is to design and construct an array detector scanning system and to determine the optimal scanning time to achieve the lowest uncertainty. To investigate the non-uniformity by our proposed method and the traditional method, our detector consisted of eight photodiodes mounted on an arm of a linear motion lead screw to guide the detector scaning onto the lighting area. A microcontroller applied for controling and measuring light irradiance in 64 points corresponding to IEC 60904-9 standard. The results showed that the array detector scanned at a speed of 33.33 mm/s to obtain the non-uniformity with the lowest uncertainty, less than 0.6%. Analysis results of the non-uniformity obtained from our system on the test areas of (mm×mm) 156×156, 166×166 and 200×200 compared with the single detector. It showed that the mean absolute error was 1.27. Our system provided a lower uncertainty than the traditional method. The measurement accuracy was acceptable. The advantage is for testing on different test areas within a single device. The measurement time is around 1/32 of the traditional method.